let n be Nat; :: thesis: for K being Field

for M1, M2 being Matrix of n,K st n > 0 & M1 commutes_with M2 holds

M1 + M2 commutes_with M2 + M2

let K be Field; :: thesis: for M1, M2 being Matrix of n,K st n > 0 & M1 commutes_with M2 holds

M1 + M2 commutes_with M2 + M2

let M1, M2 be Matrix of n,K; :: thesis: ( n > 0 & M1 commutes_with M2 implies M1 + M2 commutes_with M2 + M2 )

assume that

A1: n > 0 and

A2: M1 commutes_with M2 ; :: thesis: M1 + M2 commutes_with M2 + M2

A3: ( len M2 = n & width M2 = n ) by MATRIX_0:24;

A4: len (M1 + M2) = n by MATRIX_0:24;

A5: ( width M1 = n & len M1 = n ) by MATRIX_0:24;

width (M1 + M2) = n by MATRIX_0:24;

then (M1 + M2) * (M2 + M2) = ((M1 + M2) * M2) + ((M1 + M2) * M2) by A1, A3, A4, MATRIX_4:62

.= ((M1 * M2) + (M2 * M2)) + ((M1 + M2) * M2) by A1, A3, A5, MATRIX_4:63

.= ((M1 * M2) + (M2 * M2)) + ((M1 * M2) + (M2 * M2)) by A1, A3, A5, MATRIX_4:63

.= ((M2 * M1) + (M2 * M2)) + ((M1 * M2) + (M2 * M2)) by A2

.= ((M2 * M1) + (M2 * M2)) + ((M2 * M1) + (M2 * M2)) by A2

.= (M2 * (M1 + M2)) + ((M2 * M1) + (M2 * M2)) by A1, A3, A5, MATRIX_4:62

.= (M2 * (M1 + M2)) + (M2 * (M1 + M2)) by A1, A3, A5, MATRIX_4:62

.= (M2 + M2) * (M1 + M2) by A1, A3, A4, MATRIX_4:63 ;

hence M1 + M2 commutes_with M2 + M2 ; :: thesis: verum

for M1, M2 being Matrix of n,K st n > 0 & M1 commutes_with M2 holds

M1 + M2 commutes_with M2 + M2

let K be Field; :: thesis: for M1, M2 being Matrix of n,K st n > 0 & M1 commutes_with M2 holds

M1 + M2 commutes_with M2 + M2

let M1, M2 be Matrix of n,K; :: thesis: ( n > 0 & M1 commutes_with M2 implies M1 + M2 commutes_with M2 + M2 )

assume that

A1: n > 0 and

A2: M1 commutes_with M2 ; :: thesis: M1 + M2 commutes_with M2 + M2

A3: ( len M2 = n & width M2 = n ) by MATRIX_0:24;

A4: len (M1 + M2) = n by MATRIX_0:24;

A5: ( width M1 = n & len M1 = n ) by MATRIX_0:24;

width (M1 + M2) = n by MATRIX_0:24;

then (M1 + M2) * (M2 + M2) = ((M1 + M2) * M2) + ((M1 + M2) * M2) by A1, A3, A4, MATRIX_4:62

.= ((M1 * M2) + (M2 * M2)) + ((M1 + M2) * M2) by A1, A3, A5, MATRIX_4:63

.= ((M1 * M2) + (M2 * M2)) + ((M1 * M2) + (M2 * M2)) by A1, A3, A5, MATRIX_4:63

.= ((M2 * M1) + (M2 * M2)) + ((M1 * M2) + (M2 * M2)) by A2

.= ((M2 * M1) + (M2 * M2)) + ((M2 * M1) + (M2 * M2)) by A2

.= (M2 * (M1 + M2)) + ((M2 * M1) + (M2 * M2)) by A1, A3, A5, MATRIX_4:62

.= (M2 * (M1 + M2)) + (M2 * (M1 + M2)) by A1, A3, A5, MATRIX_4:62

.= (M2 + M2) * (M1 + M2) by A1, A3, A4, MATRIX_4:63 ;

hence M1 + M2 commutes_with M2 + M2 ; :: thesis: verum